2021
DOI: 10.15181/rfds.v28i2.1949
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approach on the Green Technologies Development

Abstract: technological innovations are a crucial component of a green economy transition and there is an urgent need to develop and implement the green technologies into the existing facilities, especially in the developing countries. the purpose of the article is to analyze theoretical approach on the green technologies development. In the article there are analyzed the essence of the concept of green economy and are identified key benefits of green technologies development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is suggested by Sneideriene & Rugine (2019) that to implement green innovations, organizations should focus on technological advances and innovations. Despite their scarcity, previous studies in the green technology literature have identified and examined multiple technological and innovation characteristics (i.e., RA, COM, COP, OB, & TR) that may affect (positively and negatively) an organization's adoption or use of GI (e.g., Kousar, Sabri, Zafar, & Akhtar, 2017;Weng & Lin, 2011;Lin & Ho, 2011).…”
Section: Technology Innovation Characteristics and Gimentioning
confidence: 99%
“…It is suggested by Sneideriene & Rugine (2019) that to implement green innovations, organizations should focus on technological advances and innovations. Despite their scarcity, previous studies in the green technology literature have identified and examined multiple technological and innovation characteristics (i.e., RA, COM, COP, OB, & TR) that may affect (positively and negatively) an organization's adoption or use of GI (e.g., Kousar, Sabri, Zafar, & Akhtar, 2017;Weng & Lin, 2011;Lin & Ho, 2011).…”
Section: Technology Innovation Characteristics and Gimentioning
confidence: 99%